NEUROETHICS - Glannon, Walter (Bioethics, 2006)
Neuroimaging, psychosurgery, deep-brain stimulation, and psychopharmacology hold considerable promise for more accurate prediction and diagnosis and more effective treatment of neurological and psychiatric disorders. Some forms of psychopharmacology may even be able to enhance normal cognitive and affective capacities. But the brain remains the most complex and least understood of all the organs in the human body. Mapping the neural correlates of the mind through brain scans, and altering these correlates through surgery, stimulation, or pharmacological interventions can affect us in both positive and negative ways. We need to carefully weigh the potential benefit against the potential harm of such techniques. This paper examines some of these techniques and explores the emerging ethical issues in clinical neuroscience.